Digitalisasi Dalam Pemasaran Produk UMKM Pasar Wisata Harmoni Keputih Surabaya - Errina Eka Yahyaningtyas; Jojok Dwiridotjahjono (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
Kuliah Kerja Nyata (KKN) Universitas Pembangunan Nasional “Veteran” Jawa Timur is an activity that is expected to be a learning tool for students to become a forum for students to actively contribute to nation building in the field of UMKM development. The main potential of UMKM in the Keputih Village is a strategic area, because of tourism and also being close to universities, making it the target market for marketing UMKM in Keputih. But there are obstacles in the process of developing and selling its products. There are culinary centers in the Keputih Village that have problems that have not implemented digital marketing, UMKM actors are still implementing conventional marketing. Based on the results of observations and observations made using the survey method, and interviews that have been carried out with the Keputih Village and UMKM actors, the main obstacle for UMKM actors is marketing. From this problem, students plan strategies to help UMKM players to capitalize on product marketing to develop UMKM businesses. As a result of this service activity, UMKM products have developed and the marketing aspects through digital are going well.